CHRONOTYPE AND DAILY FUNCTIONING OF PATIENTS WITH DIFFERENT MOTOR SUBTYPES OF PARKINSON DISEASE - A.D. Shkodina; M. Bardhan; K.A. Tarianyk; M. Yu. Delva (Проблеми екології та медицини)
Introduction. Sleep and circadian rhythm disturbances can occur at any stage of Parkinson disease (PD) and significantly affect quality of life. Chronotypes of patients with PD are associated with different phenotypes, in particular with the motor subtype. Thus, we hypothesized that patients with different motor subtypes of PD may have differences in the distribution of chronotypes and patterns of daily activity. Methods and materials. We conducted clinical research on the basis of the Centre for Parkinson Disease and Neurodegenerative Diseases of the Department of Neurological Diseases of Poltava State Medical University. PD was verified according to the recommendations of the International Movement Disorders and Parkinson's Disease Society. The motor subtype of PD was determined by the Stebbin method, which is based on the calculation of the Stebbins coefficient by the sum of the Unified PD Rating Scale scores. The examined patients were divided into 3 groups according to the motor subtype of PD: group 1 (n = 38) - patients with PD subtype with the predominance of postural instability and gait disorders (PIGD); group 2 (n = 26) - patients with PD subtype with the predominance of tremor and mixed subtype; control group (n = 30) - conditionally healthy individuals without CNS lesions. Circadian patterns were analyzed using the Munich Chronotype Questionnaire (MCTQ). Results. It was found that in PD patients sleep onset and time of getting out of bed was later (p<0.001 and p=0.042, respectively), sleep latency was longer (p<0.001), sleep duration was shorter (p=0.001), the mid-sleep corresponded to a later time (p<0.001). Patients with the PIGD subtype had a later time of getting out of bed (p=0.038), longer sleep inertia (p<0.001), shorter sleep duration (p<0.001), and later mid-sleep time (p=0.028). We have shown the tendency of patients with PD, mostly in the PIGD subtype, to later chronotypes (p<0.001). Light exposure indirectly moderately correlated with mid-sleep in all study groups. It was found that both the motor subtype (p<0.001) and the level of light exposure during the day (p<0.001) statistically significantly affect the mid-sleep. Conclusion. Thus, we have found that patients with PD differ from age-matched controls without neurodegenerative diseases by chronotype and circadian pattern of functioning. The motor subtype of the disease is associated with circadian differences, namely, the PIGD subtype is associated with shorter sleep duration, a predisposition to a later chronotype, and longer sleep inertia.